China's capitalist transformation: The rhetoric that mattered - Yuan Li (De Gruyter, 2024)
This book provides a rare account of China's market reform in the own words of the Chinese: politicians, intellectuals, the media, and journalists. The Chinese rhetoric1em1ptcomplex, ironic, argumentative, and abstruse1em1ptmay hold the key to understanding China's unique style of elite politics, state-citizen relationship, and institutional development. Topics include the establishment and change of the stock market and the recent institutionalization of the private equity industry. Rhetoricizing the Chinese capitalist transformation provides a glimpse into how the Chinese minds work as Chinese people participate in the process of changing the country and themselves. Adopting both an indigenous perspective and an outsider view on China, this book serves as a guide for anyone interested in learning how Chinese reason, persuade, debate, and resist. ; This book provides a rare account of China's market reform in the own words of the Chinese: politicians, intellectuals, the media, and journalists. The Chinese rhetoric1em1ptcomplex, ironic, argumentative, and abstruse1em1ptmay hold the key to understanding China's unique style of elite politics, state-citizen relationship, and institutional development. Topics include the establishment and change of the stock market and the recent institutionalization of the private equity industry. Rhetoricizing the Chinese capitalist transformation provides a glimpse into how the Chinese minds work as Chinese people participate in the process of changing the country and themselves. Adopting both an indigenous perspective and an outsider view on China, this book serves as a guide for anyone interested in learning how Chinese reason, persuade, debate, and resist.
Keywords: 330; China; Reform- und Öffnungspolitik; Institutionalismus; China's capitalist transformation; Rhetoric; Institutional change; Politics; Qualitative and quantitative content analysis